An Investigation into the Sex Differences Between Older Adults with Osteoarthritis in Kinetics, Kinematics, and Muscle Activation Patterns During Squatting - Zajdman, Olivia (Université d'Ottawa / University of Ottawa, 2017)
INTRODUCTION: Altered neuromuscular control and knee joint instability are commonly observed in populations with knee osteoarthritis (OA). Since knee OA is more prevalent in females, sex-related differences in muscle activation and movement strategies during activities of daily living (ADL) are theorized to be a contributing factor to the increased prevalence in females. PURPOSE: The aims of this thesis were: 1) identify sex differences in joint dynamics and muscle activation patterns in older adults with knee OA and healthy older adults; and 2) investigate whether differences in co-activation and dynamic knee joint stiffness exist between sexes in an OA and healthy populations. For both aims, squatting tasks were evaluated because it is a common and critical component in ADLs. METHODS: Thirty healthy individuals (15 females) and thirty individuals with knee OA (15 female) performed three two-legged squats at a self-selected pace on two force platforms. Hip, knee, and ankle sagittal and frontal plane joint angles, moments and powers were calculated and electromyography (EMG) of eight muscles crossing the knee joint was recorded for the test (OA affected or dominant) limb. Maximum voluntary isometric contractions were used to normalize the EMG data. Co-activation indices for six antagonist muscle pairings and dynamic knee joint stiffness (DKJS) were calculated for the acceleration and deceleration phases of squat descent and ascent. Two-way ANOVAs (Sex X OA status) were used to characterize differences in muscle activation patterns and movement strategies. RESULTS: For aim 1, decreased hip, knee and ankle sagittal plane range of motion was identified in the OA participants, with females showing the greater deficits compared to the males. Males with OA implemented a hip dominant strategy by increasing hip joint moments and decreasing knee joint moments compared to the females. Indifferent of joint status, females performed the squat with more hip adduction compared to males. Females with OA demonstrated greater hip adduction and knee valgus angles throughout the squat, contributing to the decrease in the frontal plane range of motion. Additionally, hip joint power was lower in all female participants compared to males while knee joint power was lower in the OA participants. For aim 2, females with OA, and to lesser extent males with OA had greater DKJS around peak knee flexion compared to the healthy participants. Co-activation indices revealed sex differences in neuromuscular control: Females with knee osteoarthritis had higher muscle activation magnitude and co-activation of antagonistic muscles, whereas the males used a more selective increase in hamstring co-activation and more balanced quadriceps-hamstring recruitment. CONCLUSION: Two-legged squats were able to detect sex and OA related functional deficits at the knee and adjacent hip and ankle joints. OA had a greater effect on the movement and neuromuscular control in females than males and the squat identified specific deficiencies that can be targeted for rehabilitation.
Keywords: Osteoarthritis; Sex Differences; Squat